(untitled) (International Journal of Engineering and Computer Science, 2018)
The creation of meaningful knowledge in Molecular world has been the great challenge in chemistry learning process. This paper proposed an interactive 3D design of Molecule and develops an alternative input device for interacting with it for molecules manipulation. This article describes the steps on the development of low cost data glove based on Contact switching technique. Also it shows a set of preliminary result obtain in Molecular application with the input Data Glove and discuss the use of Molecular application that could be supportive and helpful for student in chemistry learning process. The result shows that Data glove interaction is more accurate and natural than keyboard and mouse in operating 3D Molecular environment. It also enhances the user interaction in Chemistry studies and feels immersion in using Human Computer Interaction (HCI) technique